Nanocomposites based on aromatic polyesters and organically modified clay. Issue 5 (23rd May 2012) - Engelmann, G.; Bonatz, E.; Ganster, J.
Abstract Milled polybutylene terephthalate (PBT) and polytrimethylene terephthalate (PTT) were mixed with organically modified clay and extruded to prepare nanocomposites by melt intercalation. The modifier of the nanofiller belongs to the group of trialkylbenzylammonium cations. Manufacturing of the materials was carried out with a co‐rotating twin‐screw‐extruder at 230°C and 240°C for PTT and PBT, respectively. A concentration of 3% of the inorganic filler component in the composites was aimed at. The influence of mechanical stress during extrusion on the stability of the neat polymers was tested at different speeds of rotation between 100 rpm and 800 rpm. The composites were characterized with regard to the experimental filler content and the properties of the matrix polymers like melt and crystallization temperatures, degrees of crystallinity, intrinsic viscosities, and melt viscosities. Additionally, mechanical properties were analyzed by tensile tests and discussed in terms of processing and the filler presence. The dominance of PBT as polymer matrix was highlighted. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013